Hotel and restaurant industry of Ukraine: modernization, innovatization, challenges and losses of the war era - Rutynskyi, M.; Zaychenko, V.; Рутинський, М. Й.; Зайченко, В. В. (Baltija Publishing, 2025)
Since 2014, The Hotel and Restaurant Industry of Ukraine has been under the largest pressure in the world since the Second World War. The economy of the country, which has experienced large-scale aggression from the last empire of the planet, is making every effort to survive and function properly. This scientific work “sheds light” on how, over the decade of 2014-2024, The Hotel and Restaurant Industry of Ukraine not only survived, but also actively participated in the processes of transformation, modernization, innovation and building partnership relationships with consumers. The main statistical trends of the dynamics of the HoReCa sector of the Ukrainian economy are analyzed. The scale and consequences of the targeted destruction of hotel and restaurant infrastructure facilities from Odessa to Lviv by the russian army with the aim of intimidating and spreading depressive and panic moods among the population of the rear regions of the state are shown. The effectiveness of involving social networks in advertising and information popularization of restaurant business establishments is revealed. In Ukraine, over the past decade, social networks have become a field of fierce competition between hotel and restaurant establishments for the attention of potential consumers. It is social networks that form consumer motivational ratings today and provide businesses with a number of effective tools to stimulate attention to brands. This scientific work analyzes the effectiveness of involving these tools of e-promotion and e-competition in Ukraine. The effectiveness of sales of own products of Ukrainian restaurants and food enterprises through global e-commerce platforms is increasing year by year. Marketplaces have become a field of intense competition between craft producers of gastronomic products for the attention of potential consumers. The article analyzes the potential for the development of a network of craft e-shops on the Etsy platform in the current crisis realities of small businesses in Ukraine.
Готельно-ресторанна індустрія України: модернізаці, інноватизація, виклики і втрати доби війни
Keywords: нotel industry of Ukraine; restaurant industry of Ukraine; нotel industry; restaurant industry; small businesses